Effects of climate change on coffee farms: A literature review with an emphasis on Peru - Morales Rojas, Eli (2020)
The effects of climate change are creating instability in agriculture. In this sense, the purpose of this literature review article is to publicize the effects that climate change is causing on smallholder coffee farms in Peru and to describe the methods used to determine global warming, as well as alternative solutions. It is concluded that climate change is negatively affecting coffee crops, by the introduction of diseases such as rust in 2013 and 2014 decreased coffee production by 109. 500 tons (t), the effect affected the variety of coffee typica. Consequently, families have had to adapt and live with the rust; Thus, new coffee plots have been implemented, planted at higher altitudes (1500 nsnm). Likewise, the price of coffee is unstable, for the year 2013-2014 it remained S / 6.33 to S / 4.89 per kg. Faced with the difficulties that existed, the Peruvian state has encouraged the planting of coffee (catimor) from 2014 to 2018, increased by 79,755 hectares of cultivation.